Characteristics of Oil Body Development and the Cloning and Expression Analysis of PDAT Genes in Eucommia ulmoides - Jian Zhong; Jun Qing; Chenlu Liu; Qi Wang; Hongyan Du; Panfeng Liu; Lanying Du; Lu Wang; Qingxin Du (Agronomy, 2022)
Studies in multiple species have shown that phospholipid:diacylglycerol acyltransferase (PDAT) and oil bodies are important factors affecting plant oil accumulation. However, little information is available about the PDAT genes and oil bodies in Eucommia ulmoides Oliv. a high-quality oil tree. In this study, the oil bodies in Eucommia ulmoides seeds at different developmental stages were observed by frozen section technology combined with Nile red staining. It was found that there was a significant positive correlation between oil content and oil body number. In addition, seven Eucommia ulmoides PDAT (EuPDAT) genes were cloned from Eucommia ulmoides seeds based on genome data. They were assembled into three subgroups according to their classifications in Arabidopsis. EuPDAT genes in the same subgroup had similar gene structures and conserved motifs. Putative cis-element analysis of EuPDAT gene promoter regions uncovered numerous elements related to stress and plant hormones response. The expression patterns showed that EuPDAT2 and EuPDAT7 expression levels were positively related to oil content in different periods, and the correlation coefficients were 0.78 and 0.91, respectively. Our results suggest that oil body number and EuPDAT genes are important factors affecting oil accumulation in E. ulmoides seeds, and this work provides a theoretical reference for the directional cultivation of new high-oil-content E. ulmoides varieties.